2016
DOI: 10.1037/xlm0000163
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the number of changes in a display in working memory.

Abstract: Here we examine a new task to assess working memory for visual arrays in which the participant must judge how many items changed from a studied array to a test array. As a clue to processing, on some trials in the first two experiments, participants carried out a metamemory judgment in which they were to decide how many items were in working memory. Trial-to-trial fluctuations in these working memory storage judgments correlated with performance fluctuations within an individual, indicating a need to include t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 76 publications
2
34
0
Order By: Relevance
“…Previous work has demonstrated that subjective confidence strongly predicts mnemonic precision (Rademaker, Tredway, & Tong, 2012) and correlates strongly with fluctuations in trial-by-trial performance (Adam & Vogel, 2017; Cowan et al., 2016). Our finding that subjects consistently reported the best-remembered items first also suggests that subjects have strong meta-knowledge regarding the contents of working memory.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work has demonstrated that subjective confidence strongly predicts mnemonic precision (Rademaker, Tredway, & Tong, 2012) and correlates strongly with fluctuations in trial-by-trial performance (Adam & Vogel, 2017; Cowan et al., 2016). Our finding that subjects consistently reported the best-remembered items first also suggests that subjects have strong meta-knowledge regarding the contents of working memory.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that people do have awareness of the number of items that they can recall when they are explicitly asked to report this (Rademaker et al, 2012;Cowan et al, 2016). It is possible that the present task of quantifying uncertainty in recall of the tested hue may have focussed introspection on precision, rather than the number of items in memory.…”
Section: Discussionmentioning
confidence: 91%
“…In the context of memory this may be called 'metamemory'. At least to some degree, young adults have accurate metacognitive awareness of VSTM representations and fluctuation in performance across trials (Fougnie et al, 2012;Rademaker et al, 2012;Vandenbroucke et al, 2014;Cowan et al, 2016;Adam and Vogel, 2017;Suchow et al, 2017; but see Trubutschek et al, 2017 for a demonstration that non-conscious mechanisms can also support VSTM). In some situations, people are able to strategically reallocate resources across memory items (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Because participants could easily be inaccurate about their WM abilities (c.f. Cowan et al, in press), it would not be surprising if participants did not use our informed guessing formulation perfectly. This could result in bias in the estimates of P IG and potentially other parameters as well.…”
Section: Informed Guessing In the CD Taskmentioning
confidence: 99%